PENGEMBANGAN INSTRUMEN SOAL HOTS DENGAN VARIASI STIMULUS BERBASIS IT PADA MATERI KINEMATIKA - Viyanti Viyanti; Undang Rosidin; Agus Suyatna; Merry Laraswati (Program Studi Pendidikan Fisika, FKIP Universitas Sriwijaya, 2023)
This study aims to develop a High Order Thinking Skill (HOTS) question instrument with a variety of IT-based stimulus using a valid and reliable Wondershare Quiz Qreator (WQC) on kinematics material, describe the appropriate CBT settings for IT-based question instruments using this WQC, the difference in average number of students answering the questions correctly on variation of the situation used and the level of difficulty of the questions. This study uses research and development methods. The research design used was adapted from the research design of Borg & Gall with limited only to the 7th stage, namely research and data collection, product planning, initial product development, early stage trials, revision of test results, field trials, and products. end. The question instrument developed has a cognitive level of analyzing (C4), evaluating (C5), and creating (C6). Prior to field testing, the instrument was tested by experts which consisted of a material validation test with a score of 3.37 (very valid), constructs with a score of 3.16 (valid), language with a score of 3.15 (valid), and CBT settings with a score of 3.24 (valid). The research sample for field trials, namely 22 students of class X MIA MA Al-Hidayat Gerning. The results of the data obtained were analyzed with the help of SPSS software. The question instrument contains 3 very difficult questions, 9 moderate questions, and 12 very easy questions. Based on the results of the study, the HOTS test instrument developed was valid and reliable with Cronbach's alpha value of 0.874 which was in very good criteria.